A5.15 Heterogeneity in plasmacytoid dendritic cell response to HIV-GP120 as a putative cause for variability in HIV musculoskeletal co-morbidity. (13th February 2015) - Cooles, FAH; Anderson, AE; Hilkens, CMU; Isaacs, JD
Abstract : Background and objectives: Musculoskeletal presentations following initial HIV infection, although variable, cause significant morbidity. gp120 is a HIV surface glycoprotein and plasmacytoid dendritic cells (pDCs) are one of the first cells to encounter gp120 aided by their high expression of CD4. pDCs produce large amounts of interferon alpha (IFN-alpha) following Toll like receptor (TLR) stimulation and their role in rheumatic disease is of increasing interest with IFN-alpha being implicated in subsets of inflammatory arthropathies. Some studies suggest an immunomodulatory role of gp120 by inhibiting pDC TLR9 induced IFN-alpha production. Given the variability in incidence of HIV associated musculoskeletal presentations we hypothesised that heterogeneity in response to gp120, and hence heterogeneity of IFN-alpha production, may contribute to variability in clinical presentation following acute HIV infection. Materials and methods: Peripheral blood mononuclear cells (PBMCs) were separated from healthy donor blood samples using density centrifugation. pDCs were isolated from PBMCs by MACS magnetic isolation using the CD304 + positive selection kit. Purity was measured by co-expression of CD303 and CD123 by flow cytometry. pDCs and PBMCs were both cultured in RPMI supplemented with 10% fetal calf serum +/- gp120 and CPG-A for 18 h (6 h for intracellular staining). gp120 (MN strain) and TLR9 agonist CPG-A (ODN 2216) were used at varying concentrations in these cultures. IFN-alpha production was measured by flow cytometry (intracellular IFN-a stain) or ELISA (from culture supernatant). sCD4 (10ug/ml) was included in some experiments. Results: We recruited 12 healthy volunteers and pDC purity following isolation consistently >90%. In both pDC and PBMC cultures gp120 by itself did not induce IFN-alpha production. However in PBMC cultures when cultured with CPG-A and gp120 66.67% of individuals (n = 8) demonstrated a dose dependant increase in IFN-alpha production when compared with CPG-A alone. However in the remaining 33.33% (n = 4) the inverse trend was seen. Similar patterns were seen for both intracellular IFN-alpha staining as well as extracellular production (ELISA). When comparing the effect of sCD4 (n = 4), an inhibitor of gp120 binding, we showed that the effects of gp120 on CPG-A induced INF-alpha production were reduced. These trends were replicated in isolated pDC cultures. Conclusions: We demonstrate significant heterogeneity in response to simultaneous TLR9 signalling and exposure to gp120 in a healthy population. This may replicate heterogeneity in pDC response to acute HIV infection and TLR9 stimulation in vivo . This heterogeneity may, in turn, contribute to the rheumatic disease phenotype in acute HIV infection, and provide insight into novel therapeutics.